The expanded space-based component of the Global Observing System and the role of the coordination group for Meteorological Satellites - HINSMAN, DONALD E. (MAUSAM, 2003)
The space-based component of the Global Observing System and its in situ counterpart form the World Weather Watch’s Global Observing System. The Global Observing System (GOS) was established during the formation of the World Meteorological Organization (WMO) World Weather Watch (WWW). During the nearly four decades since the formation of the WWW, the space based component of the GOS evolved from a constellation of one or more polar-orbiting meteorological satellites to two constellations comprised of at least two near-polar-orbiting satellites and at least five geostationary environmental observation satellites. Recently, a third constellation of appropriate Research and Development satellites has been added. This paper provides an historical description of the space-based configuration of the GOS and the role that the Coordination Group for Meteorological Satellites (CGMS) has had in its implementation. Fundamental to the space-based configuration has been WMO user requirements. The WMO technical commission with the lead responsibility for the World Weather Watch is the Commission for Basic Systems (CBS). CBS has developed a review process to compare user requirements for WMO programmes and WMO supported programmes with expected observing system capabilities. The evolution of user requirements has resulted in the need for a review of the present configuration of the space-based global observing system. CBS has decided to use its review process to evaluate user requirements and anticipated capabilities in order to propose an evolution of the present configuration. This paper also describes the review process and recent WMO decisions that are part of a concerted effort to provide a GOS for the following decades capable of meeting the stringent and increasing demands of WMO members.